INNV-43. IMPROVING POST OPERATIVE FOLLOW-UP AND TIME TO ADJUVANT TREATMENT FOR HIGH GRADE GLIOMA. (11th November 2019) - Catalino, Michael; Zeitouni, Daniel; Henretty, Sonja; Zhu, Anqi; Khagi, Simon
Abstract: BACKGROUND: High grade glioma patients are prone to lapses in treatment due to the complexities related to coordination of care, the timing of adjuvant treatment, and insurance barriers. The purpose of this study was to determine the impact of an institutional multidisciplinary protocol on transitions of care after surgery for high grade gliomas between 2015 and 2018. METHODS: A retrospective cohort study was conducted using CPT codes for enrolled glioma patients between 2015–2018 with unplanned surgery. Historical controls were compared to the intervention group which began enrollment in November 2016. We used time-to-event analysis to compare time to neuro-oncology follow up and time to adjuvant treatment (radiation and/or chemotherapy). The effect of discharge disposition and insurance status was also assessed. The study incorporated an ad hoc analysis of survival outcomes. RESULTS: The intervention and control groups had similar baseline characteristics. The intervention was associated with more patients following up with neuro-oncology within 2 weeks (51.1% in intervention group compared to 30.0% in control group), more patients starting radiation within 30 days (43.6% and 25.0%, respectively) and more patients starting chemotherapy within 30 days (59.0% and 35.0%, respectively). Time-to-event analysis revealed that the intervention trended toward earlier initiation of chemotherapy (p=0.076). Only 16.7% of patients discharge to a skilled nursing facility were able to initiate chemotherapy at the 30-day mark. Time-to-event analysis revealed that insurance status was significantly associated with initiating chemotherapy at the 30-day mark (p=0.023). Survival analysis is planned and will be reported in a future manuscript. CONCLUSION: A multidisciplinary approach to capturing patients after surgery decreases time to follow up with neuro-oncology and initiation of adjuvant treatment. Timely follow up is associated with insurance status, discharge disposition, and multidisciplinary discussions between the treatment team and ancillary staff. Survival outcomes are being assessed and will be reported.